PERBEDAAN SALINITAS MEDIA TERHADAP EFISIENSI PEMANFAATAN PAKAN BENIH IKAN NILA GIFT (Oreochromis sp) - Silvia Rosdianasari, M.B; Syakirin .; Komariyah . (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2013)
This  study  aimed  to  determine  the  effect  of  the  differences  and  optimal  salinity  levels  on  the efficiency  of  feed  utilization  in  Oreochromis  sp.  Method  used  in  this  study  is  the  experimental laboratory methods. Research carried out by completely randomized design with 4 treatments and 3  replications. The  treatment  includes  a  treatment  with  0  ppt  salinity,  Treatment  B:  5  ppt, Treatment C: 10 ppt, Treatment D: 15 ppt.Differences in the low salinity culture media failed to give a positive response to the efficiency of feed utilization of fish seed is cultivated. Decreasing salinity is used, it will affect the efficiency of feed utilization of tilapia seed. In the C treatment (10 ppt  salinity)  gives  the  maximum  response  to  the  efficiency  of  feed  utilization    Oreochromis  sp. which,  at  85.95%  followed  by  treatment  D  (74.26%),  treatment  B  (58.68%)  and  treatment A (48.49%). Treatment differences in salinity media on the efficiency of feed utilization Oreochromis s.  produces a quadratic curve with equation Y = 45.69 + 5.37 X - 0.22 X2. Water quality of the media during the study the water temperature is 25 - 28oC, pH 7.3, and DO from 4.5 to 5.6 ppm, so it is still within the range appropriate for the survival of Oreochromis sp. Keywords: salinity, the efficiency of feed utilization